New developments in prenatal diagnosis of congenital adrenal hyperplasia. Issue 165 (January 2017) - Kazmi, Diya; Bailey, Jack; Yau, Maggie; Abu-Amer, Wahid; Kumar, Ameet; Low, Merly; Yuen, Tony
Highlights: Dexamethasone treatment before 9 gestational weeks prevents virilization in females affected with classical CAH. Prenatal dexamethasone treatment has little to no adverse side effects. Noninvasive methods using fetal DNA from maternal blood have been developed for early prenatal genetic testing. Early noninvasive prenatal genetic testing avoids prescription of dexamethasone to mothers carrying male or unaffected female fetuses. Abstract: Congenital adrenal hyperplasia (CAH) owing to 21-hydroxylase deficiency is an autosomal recessive disorder caused by mutations in the CYP21A2 gene. Females affected with classical CAH are at risk for genital ambiguity, but can be treated in utero with dexamethasone before 9 gestational weeks to prevent virilization. Early genetic diagnosis is unavailable through current invasive methods of chorionic villus sampling and amniocentesis. New developments in prenatal genetic testing utilize fetal DNA extracted from maternal blood through noninvasive methods, which allow the determination of fetal gender and the diagnosis of CAH at an early gestational age (<9 weeks). Noninvasive prenatal diagnosis allows for the establishment of early and effective management plans in fetuses at risk for CAH and avoids unnecessary prenatal dexamethasone treatment